2016
DOI: 10.1186/s12610-016-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study about infertile men’s awareness of their reprotoxic exposures and the intervention of occupational medicine to assess them

Abstract: BackgroundMale infertility related to professional reprotoxic exposure has been assessed in several studies. Collaboration between occupational physicians and patients can yield information about the preventive measures that can be taken to avoid such exposure. The use of preventive measures is determined by the collaboration between reproductive medicine and occupational medicine and also by the patient’s awareness of reprotoxic occupational exposures. Our andrology laboratory developed a systematic environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There are many existing studies on the knowledge and perceptions of women concerning their exposure to teratogenic agents during pregnancy, reporting a low level of knowledge [ 24 28 ]. However, there is no corresponding data on men and couples in general, especially subfertile ones, besides the pilot study of Christiaens et al [ 19 ] suggesting that most of subfertile men were unaware of their exposure to environmental reprotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many existing studies on the knowledge and perceptions of women concerning their exposure to teratogenic agents during pregnancy, reporting a low level of knowledge [ 24 28 ]. However, there is no corresponding data on men and couples in general, especially subfertile ones, besides the pilot study of Christiaens et al [ 19 ] suggesting that most of subfertile men were unaware of their exposure to environmental reprotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors associated with a high desire of subfertile women to reduce their exposure were medical factors (decreased ovarian reserve), education (preconception directives) and financial factors [ 21 ]. Regarding subfertile men, we previously suggested that the most common reasons for exposure modification were related to semen parameters impairment and known professional exposure [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations